‘Idiopathic’ partial androgen insensitivity syndrome in 28 newborn and infant males: impact of prenatal exposure to environmental endocrine disruptor chemicals? - Gaspari, Laura; Paris, Françoise; Philibert, Pascal; Audran, Françoise; Orsini, Mattea; Servant, Nadège; Maïmoun, Laurent; Kalfa, Nicolas; Sultan, Charles (European journal of endocrinology, 2011)
Objective46,XY disorders of sex differentiation (46,XY DSD) can be due to a testis determination defect, an androgen biosynthesis defect, or androgen resistance (complete or partial androgen insensitivity syndrome (PAIS), or 5α reductase deficiency). We aimed to evaluate the impact of a prenatal contamination by environmental xenoestrogens in ‘idiopathic’ PAIS-like phenotype.SubjectsWe investigated 28 newborn/infant males with 46,XY DSD, normal androgen production, and no androgen receptor or steroid-5αR type II enzyme (SRD5A2) gene mutations.MethodsTo exclude other genetic defects, we sequenced the steroidogenic factor 1 (SF1) and mastermind-like domain-containing 1 (MAMLD1) genes, which were recently found to be associated with the PAIS-like phenotype. Parents were interviewed about their environmental/occupational exposure to endocrine disrupting chemicals (EDCs) before/during the patients' fetal life. Total estrogenic bioactivity of patient serum was analyzed by ultrasensitive bioassay.ResultsAll the patients had normal SF1 sequence and one patient showed a double polymorphism of MAMLD1. Eleven (39.3%) of the 28 patients had reported parental fetal exposure to EDCs. The mean estrogenic bioactivity in these 11 patients with fetal EDC exposure (6.65±8.07 pg/ml) versus 17 cases without contamination (1.27±0.34 pg/ml) and controls (1.06±0.44 pg/ml; P<0.05) was elevated.ConclusionsOur results indicate that the ‘idiopathic’ PAIS-like phenotype may in some cases be related to EDC contamination during fetal life.